Translation Techniques Used in Translating the Captions of Ani Yudhoyono’ Instagram - Munjiah Hayati; Syahron Lubis; Rahmad Husein (LINGUISTIK TERAPAN, 2018)
The objectives of this study were to classify the types of translation techniques used in translating the captions of Ani Yudhoyono’s Instagram, to describe how the techniques are used in translating the captions of AniYudhoyono’sInstagram, and  to find out the reason of using the technique in translating the captions of AniYudhoyono’s Instagram. The data were 226 captions (words and sentences) collected weekly written by Ani Yudhoyono in her Instagram account in. This research applied Qualitative Research design. The data were collected through reading and analyzing the source language and her translation in the target language. Another five was not exist. It was happen because there were some captions that were not able translated by applying those techniques in order to keep the sense of language itself.The most dominant technique used was Literal technique consisting of 54 data. In another word, it has 23.89% of the frequency, Compensation with  25 data (11.06%), Modulation with 19 data (8.40%), Transposition with 18 data (7.96%), Borrowing with 16 data (7.07%), Calque with 16 data (7.07%), Adaptation with 15 data (6.63%), Description with 14 data (6.19%), Reduction with 14 data (6.19%), Linguistic compression with 12 data (5.30%), Amplification with 11 data (4.86%), Particularization with 5 data (2.21%), and Generalization with 4 data (1.76%). While in the double techniques, the translator used Borrowing+Transposition with 1 data (0.44%), Calque+Amplification with 1 data (0.44%) and the last is Transposition+Calque with 1 data (0.44%).In this study, the translator doesn’t only apply single technique in a sentence (caption), but she also applied double technique in five of the data.Keywords: Translation Technique, Instagram, Molina and Albir, Caption, Bilingual